Program uroczystości "Święta Oświaty" w Gdyni w dniu od 1-3 maja 1946 r. (Gdynia : [s.n.], 1946)
Afisz z programem uroczystości.
Keywords: Święta -- Polska -- Gdynia -- 1945-1970 -- druki ulotne; Edukacja -- Polska -- Gdynia -- 1945-1970 -- druki ulotne; Gdynia (Polska) -- 1945-1970 -- druki ulotne; Gdynia (Polska) -- 1945-1970 -- źródła